Improvement of heat stress tolerance in soybean (Glycine max L), by using conventional and molecular tools - Jianing, Guan; Yuhong, Gai; Yijun, Guan; Rasheed, Adnan; Qian, Zhao; Zhiming, Xie; Mahmood, Athar; Shuheng, Zhang; Zhuo, Zhang; Zhuo, Zhao; Xiaoxue, Wang; Jian, Wei (Frontiers in Plant Science, 2022)
The soybean is a significant legume crop, providing several vital dietary components. Extreme heat stress negatively affects soybean yield and quality, especially at the germination stage. Continuous change in climatic conditions is threatening the global food supply and food security. Therefore, it is a critical need of time to develop heat-tolerant soybean genotypes. Different molecular techniques have been developed to improve heat stress tolerance in soybean, but until now complete genetic mechanism of soybean is not fully understood. Various molecular methods, like quantitative trait loci (QTL) mapping, genetic engineering, transcription factors (TFs), transcriptome, and clustered regularly interspaced short palindromic repeats (CRISPR), are employed to incorporate heat tolerance in soybean under the extreme conditions of heat stress. These molecular techniques have significantly improved heat stress tolerance in soybean. Besides this, we can also use specific classical breeding approaches and different hormones to reduce the harmful consequences of heat waves on soybean. In the future, integrated use of these molecular tools would bring significant results in developing heat tolerance in soybean. In the current review, we have presented a detailed overview of the improvement of heat tolerance in soybean and highlighted future prospective. Further studies are required to investigate different genetic factors governing the heat stress response in soybean. This information would be helpful for future studies focusing on improving heat tolerance in soybean.